A new genus and species of the Dasybatotreminae Bychowsky, 1957 (Monogenea: Monocotylidae), parasitic on Hypanus dipterurus (Jordan & Gilbert) (Myliobatiformes: Dasyatidae) in the Southeastern Pacific Ocean off Peru - Chero, Jhon D.; Cruces, Celso L.; Sáez, Gloria; Luque, José L. (Zootaxa, 2018)
Peruanocotyle n. gen. is proposed to accommodate Peruanocotyle chisholmae n. sp. (Monogenea: Monocotylidae). The new species is a gill parasite of the diamond stingray, Hypanus dipterurus (Jordan & Gilbert) (Myliobatiformes: Dasyatidae), a demersal chondrichthyan collected off the coast of Callao, Peru. Peruanocotyle n. gen. is placed in the Dasybatotreminae Bychowsky, 1957 because its anterior attachment organ has multiple glandular openings. Peruanocotyle chisholmae n. gen., n. sp. is unique among the Dasybatotreminae, by having: a well-developed, broadly ovoid anterior attachment organ with numerous grooves and an anteromedial notch; three prominent anterior glands that are connected to numerous peripheral glands; an unusual whip-shaped male copulatory organ composed of four connate tubes; an ejaculatory duct with slightly sclerotized walls where the proximal end has criss-crossed creases and the distal portion is highly convoluted; an ejaculatory bulb with one bipartite internal seminal vesicle; a wheel-shaped haptor with one central loculus and eight peripheral loculi; anchors that are much shorter than the width of marginal membrane and have an accessory sclerotized piece present; four oval testes, arranged in two groups; an ovary that has six clavate, proximal lobules and a distal portion that is strongly coiled; intestinal ceca with large lateral and medial diverticula; an oral opening surrounded by numerous small dome-like papillae; and a single vagina with sclerotized walls. Dasybatotreminae is amended to accommodate the new genus, and the new species is fully described and illustrated herein. The present finding adds to the other three marine monocotylids previously reported from Peru, namely Anoplocotyloides chorrillensis Luque & Iannacone, 1991; Anoplocotyloides papillatus (Doran, 1953) Young, 1967 and Monocotyle luquei Chero, Cruces, Iannacone, Sanchez, Minaya, Sáez & Alvariño, 2016.